(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Rural tourism is gaining importance in Indian tourism with its economic and social benefits it is estimated that Rs. 4,300 Crore additional revenue can be generated through rural tourism. This is going to play a vital role in bridging the gap between Rural and Urban India by balancing urbanization and counter urbanization by creating Jobs that typically occurs in the hotel and Catering trades, but can also take place, in transport, retailing and in heritage interpretation. Farmhouse accommodation can create jobs even the Caravan Campsites are yielding Jobs and revenue. Rural tourism means any form of tourism that showcases the rural life, art culture and heritage at rural locations. There by benefiting the local community economically and socially as well as enabling interaction between the tourists and the locals for a more enriching tourism experience that can be termed as rural tourism Rural tourism cash flows can assist job retention in services such as retailing, transport hospitality and medical care. it also provides additional income for farmer and in some cases, for foresters and fisherman Job retention is not as politically glamorous as Job creation, but helps the Viability of small communities for the survival of marginal areas. It is multi-faceted and may entail farm / agricultural tourism, Cultural tourism ,nature tourism, adventure tourism, and eco tourism also. The tourism industry often promotes an exciting and growing industry suited to the energies and enthusiasm of young people. Career options are enhanced with the opportunities for training and direct involvement in running tourism businesses, especially those within small communities.